Problematic Internet Use: Deficient Self-Regulation Or Pathology? - Shumaila Yousaf Zai; Uzma Javed; Mirellayani De Soriano (Paradigms, 2012)
Increasing research on problematic internet use (PIU) makes it necessary to distinguish between the generalized use of internet and its specific applications. This study explores the relationships amongst psychosocial vulnerabilities, specific PIU (SPIU), generalized PIU (GPIU), time spent online (general and specific), and negative outcomes in a sample of British young adults. The results indicate that both SPIU and GPIU are caused by psychosocial vulnerabilities. However, in the case of specific internet applications, these vulnerabilities foster deficient self-regulation (SPIU), leading to excessive time spent online, which produces negative outcomes. Conversely, in the case of generalized use of internet, it is GPIU as pathology, rather than excessive time spent online on general activities, which leads to negative outcomes.